Synthesis of silk fibroin-glycopolypeptide conjugates and their recognition with lectin - Das, Soumen; Pati, Debasis; Tiwari, Neha; Nisal, Anuya; Sen Gupta, Sayam (Biomacromolecules, 2012)
Silk fibroin (SF), the natural fibrous protein created by the Bombyx mori silk worm, is being increasingly excellent mechanical strength, high oxygen/water permeability, excellent mechanical strength; high oxygen/water:permeability, and biocompatibility: :It is also well known that surface. modification of SF, With Organic ligands such as the extracellular protein :binding. Arg-Gly-Asp, (RGD) peptides:,: help adhesion and,proliferation. of cells better-a key; requirement for it to function as extracellular. matrices; In this, Work, We have conjugated synthetic glycopolypeptides (GPs) that were synthesized by controlled ring opening polymerization of alpha-manno-lys N-carboxyanhydrides (NCAs) onto SF by using Cu catalyzed click reaction to synthesize 1 a new hybrid :Material (SF GP), Which We believe will have :both the mechanical properties of native SF and the molecular recognition property of the carbohydrates in the GP. By controlling the :amount of GP grafted onto SF, we have made three SF GP conjugates that differ in their ability to assemble into films. SF GP conjugates having a very high content of GP formed completely water soluble brush like polymer that displayed very high affinity toward the lectin concanavalin-A (Con-A) Films cast from SF-GP conjugates using lower amounts of grafted GP were more stable in water, and the stability can be modulated by varying the amount of G grafted. The water insoluble film SF-GP(25) was also found to bind to fluorescently labeled Con A, as was seen by confocal microscopy Such SF-GP hybrid films may be useful as mimics of extracellular matrices for tissue engineering:

Synthesis of end-functionalized phosphate and phosphonate-polypeptides by ring-opening polymerization of their corresponding N-carboxyanhydride - Das, Soumen; Kar, Mrityunjoy; Sen Gupta, Sayam (Polymer Chemistry, 2013)
Phosphopolypeptides provide an interesting biomimetic analog for phosphorylated proteins that are involved in biomineralization. We have developed a high yielding synthesis of cysteine-based phosphate and phosphonate N-carboxyanhydride (NCA) by using the thiol-ene coupling reaction. These phosphate and phosphonate NCA monomers underwent polymerization using simple primary amine initiators to form well defined homophosphopolypeptides. Using a bifunctional initiator we were able to install a ``clickable'' alkyne or azide group at the end of the polypeptide chain. We were also able to successfully synthesize fully water-soluble phosphonate based polypeptides by hydrolysis of the corresponding phosphonate ester groups in the polypeptide. These water-soluble phosphopolypeptides adopt a random coil conformation at physiological pH.

Synthesis of phospho-polypeptides via phosphate-containing N-carboxyanhydride: application in enzyme-induced self-assembly, and calcium carbonate mineralization - Mondal, Basudeb; Das, Soumen; Panda, Sidharth; Dutta, Tahiti; Sen Gupta, Sayam (ChemPlusChem, 2020)
An easy synthetic strategy was developed to synthesize the phosphate-functionalized amino acid N-carboxyanhydride (NCA), using simple primary amine initiators to obtain homo and block phospho-polypeptides with controlled molecular weight and molecular weight distribution. The methodology was extended to the synthesis of the end-functionalized homo polypeptides (15 to 50 repeat unit) and block co-polypeptides with PEG (0.7 K, 2 K, and 5 K) and glycopolypeptide (15-unit mannose glycopolypeptide) as one of the blocks. The deprotected fully water-soluble anionic phosphate-based polypeptides showed pH-dependent helical conformation with a helical content of 20 %, which further changed to beta-sheets upon addition of the enzyme alkaline phosphatase (ALP) due to dephosphorylation. The block co-polypeptide containing PEG as one of the blocks led to its self-assembly into colloidal structures, such as vesicles with a hydrodynamic diameter of similar to 250 nm, due to the formation of amphiphilic block co-polymer upon dephosphorylation. The nature of the colloidal structures formed can be temporally controlled by the extent of dephosphorylation. Finally, the phospho-polypeptides serve as a template for the mineralization of calcium carbonate with varying polymorphs and morphologies.
Keywords: Biomineralization; enzymes; phosphopolypeptides; Proteins; Self-assembly